Understanding MSMEs’ Intentions to Apply for Formal Loans Through Behavioral Perspectives: Memahami Niat UMKM untuk Mengajukan Pinjaman Formal melalui Perspektif Perilaku - Tri Utomo Prasetyo; Alivia Meyrizka Utami; Siti Resmi (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2026)
This study explores the factors influencing Micro, Small, and Medium Enterprise (MSME) owners’ intentions to apply for formal loans in Indonesia by integrating financial literacy and perceived access to finance into the Theory of Planned Behavior. Using a quantitative approach, data was collected from 215 MSME owners and analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM). Results show that financial literacy, perceived access to finance, and attitudes toward formal loans significantly increase loan application intentions—indicating that more financially capable owners and those with positive perceptions of formal credit are more likely to apply. Interestingly, perceived difficulties in accessing finance actually increase intention, suggesting a need-driven response. In contrast, social norms and perceived behavioral control have negligible effects. These findings highlight the importance of strengthening financial education, reshaping perceptions of credit accessibility, and improving attitudes toward formal financing. The study recommends policy initiatives that simplify loan processes, expand inclusive financial programs, and enhance financial literacy to better support MSME growth in Indonesia.